Compare the Effectiveness of Ayurveda Brand with Global Brand in Market (International Journal of Innovative Research in Engineering & Management, 2021)
India is a significant market for the Fast-Moving Consumer  Goods (FMCG) businesses because of its vast population.  There are numerous large and small companies currently  operating and having considerable impact on the industry. The  current paper has been prepared to evaluate the development  of Ayurveda brand so quickly in the industry, it is obvious  that this trip of Ayurveda was not an easy job as Ayurveda being very much new. But the method of positioning,  branding and eventually strategy to build a confidence and  trust in customer make a difference and Ayurveda’s market  share was so fast that it has over take many goods of  renowned brand in only 2 to 3 years and emerge as a market  leader. The marketing strategy of Swami Ramdev was  executed so beautifully in market and his major formula was  “swadeshi” that has created a magic and attract a good  number of consumers along with a good number of raw  material supplier’s i.e., Indian farmer. There is a need to  promote the indigenous grown and produced goods.
Keywords: Customer; Consumer; Foods; Ayurveda; Swadeshi